Expression profiling of rectal biopsies suggests altered enteric neuropathological traits in Parkinson’s disease patients - Cossais, François; Schaeffer, Eva; Heinzel, Sebastian; Zimmermann, Jessica; Niesler, Beate; Röth, Ralph; Rappold, Gudrun; Scharf, Amelie; Zorenkov, Dmitri; Lange, Christina; Barrenschee, Martina; Margraf, Nils Gerd; et al. (Journal of Parkinson's Disease, 2021)
Still little is known about the nature of the gastrointestinal pathological alterations occurring in Parkinson’s disease (PD). Here, we used multiplexed mRNA profiling to measure the expression of a panel of 770 genes related to neuropathological pro